The population ecology of undesigned systems: An analysis of the Arizona charter school system - Matthew M. Mars; Judith Bronstein (Journal of Organization Design, 2020)
The application of ecological concepts and principles to the study of organization design and system development is now commonplace. Population ecology is one biological perspective that has been especially influential within the organization design literature. In the current study, we illustrate for the first time how this framework can be used to reveal when and in what ways intervention is warranted within a system that, like a biological population in nature, has emerged with little to no purposeful design. Specifically, we use 20 years of data on 1,074 Arizona charter schools to illustrate how population analysis can be used to uncover the characteristics of individual organizations that have the highest ability to survive over time within systems that have been allowed to emerge with little to no purposeful design. Our findings lead us to argue how pre-intervention population analysis at the system level can influence organization-level design choices in a way that enables dynamic fit and thereby enhances the likelihood of organization survivorship and innovation over time.
Keywords: 650; Inter-organizational dynamics; Population ecology; dynamic fit